Green Legal Theory - M’Gonigle, Michael (Ökologisches Wirtschaften - Fachzeitschrift, 2008)
Green thinking has been established both in theory and practice in Europe for decades, far ahead of North America. Few on the western side of the Atlantic understand that "green” is much more than just progressive public policy. It is about a new social framework.